Study on providing public transport in cross-border regions. Mapping of existing services and legal obstacles. Rail link Lille (France) - Tournai (Belgium). Case study report - Europäische Kommission, Generaldirektion Regionalpolitik und Stadtentwicklung (Publications Office of the European Union, 2022)
This case study report presents the business model for the cross-border rail service between Lille (France) and Tournai (Belgium). This report is part of a series of 31 case studies developed in the framework of the study ‘Providing public transport in cross-border regions – Mapping of existing services and legal obstacles’. Spatial Foresight in cooperation with TCP international, TRT trasporti e territorio and EureConsult completed this study for the European Commission’s DG REGIO. The case studies highlight a variety of business models for cross-border public transport services. This includes governance arrangements and operational provisions to develop the service and address demand in border regions. These aspects will be introduced in section 2, as well as the territorial scope of the service. Section 3 presents key obstacles related to the business model as well as solutions. Section 4 is about lessons learnt from this case. This case study illustrates how the EGTC Eurometropolis Lille-Kortrijk-Tournai contributes, as a cross-border entity, to improving services for the rail connection Lille – Tournai, and encouraging key stakeholders to consider their role to offering services for the cross-border region. The Lille – Tournai connection is part of a network of cross-border public transport services contributing to further integration of the region across national, regional and language borders. The Eurometropolis facilitates governance processes and aims to develop an ecosystem of sustainable transport in which public transport plays an important role. In doing so, the Eurometropolis often has to initiate and adopt practical solutions. This case study is based on desk research including sources from French and Belgian sides of the border as well as studies covering the cross-border region. One interview was conducted with a representative from the Eurometropolis Lille-Kortrijk-Tournai, responsible for the working group “mobility, employment and local services”. The interviewee provided insights on the rail connection and its function in the cross-border region and its public transport connection from a cross-border point of view.
Keywords: Eisenbahn; Eisenbahnlinie; Eisenbahnverkehr; Eurométropole Lille-Kortrijk-Tournai; Öffentlicher Personennahverkehr

Europäische Integration und Europa der Regionen. Überlegungen zur Geschichte der grenzüberschreitenden Zusammenarbeit in den Beziehungen Belgiens und Nordrhein-Westfalens - Brüll, Christoph (Geschichte im Westen, 2015)
Keywords: Europäische Integration; Grenzüberschreitende Kooperation; Nordrhein-Westfalen